2020
DOI: 10.1371/journal.pbio.3000840
|View full text |Cite
|
Sign up to set email alerts
|

Cortical tracking of speech in noise accounts for reading strategies in children

Abstract: Humans' propensity to acquire literacy relates to several factors, including the ability to understand speech in noise (SiN). Still, the nature of the relation between reading and SiN perception abilities remains poorly understood. Here, we dissect the interplay between (1) reading abilities, (2) classical behavioral predictors of reading (phonological awareness, phonological memory, and rapid automatized naming), and (3) electrophysiological markers of SiN perception in 99 elementary school children (26 with … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(50 citation statements)
references
References 123 publications
(199 reference statements)
9
41
0
Order By: Relevance
“…Table 1 shows that all groups had similar IQ and socio-economic status, that dyslexic readers compared with age-matched controls had about the same age and lower reading scores, and that dyslexic readers compared with reading-level-matched controls were older and had similar reading scores. A previous analysis of the reading scores also revealed that our dyslexic readers had a rather homogenous reading profile, characterized by similar reading difficulties in the two reading pathways (Destoky et al 2020).…”
Section: Participantssupporting
confidence: 63%
See 4 more Smart Citations
“…Table 1 shows that all groups had similar IQ and socio-economic status, that dyslexic readers compared with age-matched controls had about the same age and lower reading scores, and that dyslexic readers compared with reading-level-matched controls were older and had similar reading scores. A previous analysis of the reading scores also revealed that our dyslexic readers had a rather homogenous reading profile, characterized by similar reading difficulties in the two reading pathways (Destoky et al 2020).…”
Section: Participantssupporting
confidence: 63%
“…Finally, concerning the severity of the reading deficit of the included children with dyslexia, the phonological deficit is more commonly seen in severe than mild dyslexia (Saksida et al, 2016). Also along this line, reading abilities correlate with some aspects of CTS in noisy conditions (Destoky et al, 2020). Yet, none of the previous studies assessing CTS in dyslexia (Di Liberto et al, 2018a;Lizarazu et al, 2021a;Molinaro et al, 2016a;Power et al, 2016a) considered the possibility that CTS is altered only in the most severe form of dyslexia.…”
Section: Introductionmentioning
confidence: 89%
See 3 more Smart Citations